Structure of The Sibling Inventory of Differential Experience-Chinese Version (SIDE-C): a bifactor model approach - Ong, Anna Wen Huey; Tan, Chee-Seng (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Sibling Inventory of Differential Experience (SIDE; Daniels & Plomin, 1985) is a self-report to assess children’s perception of parental differential treatment (PDT). Specifically, SIDE measures two specific constructs of PDT: control and affection. The present study applied both the traditional (two-correlated-factor model) and novel (bifactor) modeling approaches to derive the most optimal measure-ment structure of the Chinese version of SIDE (SIDE-C). Respondents were 225 primary school stu-dents who have only one sibling in the family. Results showed that, while the two-correlated-factor model was acceptable, the bifactor model had a better fit. The bifactor model is preferable in terms of fit indices and the principle of parsimony. Additionally, Omega hierarchical coefficient supported the strength of the general factor over the specific factors of parental differential treatment. The findings not only shed light on the factorial validity of the SIDE-C but also suggest future studies to consider the roles of the general and specific factors of PDT.